MODIFICATION OF EPOXY-AMINE POLYMERS BY OLIGOHEXAMETHYLENEGUANIDINES - I. N. Senchikhin; E. S. Zhavoronok; E. V. Kharitonova; V. I. Roldugin (Тонкие химические технологии)
Methods of introducing a water-soluble biocide modifier, oligohexamethyleneguanidine hydrochloride, into epoxy-amine systems were studied. The obvious way is the introduction of the modifier in the waterborne epoxy-amine systems. However, this leads to cured systems with reduced mechanical properties. Introduction of oligohexamethyleneguanidine hydrochloride solutions in organic solvents into epoxy-amine systems allows obtaining a homogeneous system, but their application is limited by the presence of a volatile solvent. Finally, introduction of oligohexamethyleneguanidine hydrochloride solutions in a water-soluble amine curing agent into epoxy-amine systems has good prospects. It is shown that the analyzed modifier has good solubility in ethylenediamine, but poor solubility in oligooxypropylenediamine. It was found that the modifier is capable of interacting chemically with epoxy resins at 22°C to form an elastic insoluble material. In an epoxy-amine system with a more active hardener (ethylenediamine) oligohexamethyleneguanidine hydrochloride acts as a plastifier (flexibilizer). This significantly reduces the glass transition temperature of the matrix (from 53 to 37ºC).